Implementation of Edmodo and Classdojo on the Activeness and Achievements of Students during Covid-19 Pandemic in Learning Mathematics - Rismi Annisa; Teguh Wibowo; Mujiyem Sapti (Jurnal Iqra' : Kajian Ilmu Pendidikan, 2022)
The transfer of learning in schools from online learning to online learning had a considerable impact in various sectors throughout the country. Education in Indonesia in particular, student activity and learning achievement are low along with the implementation of online learning. Students are more accustomed to learning task systems. This study analyzes student learning activity and achievement in learning mathematics during the Covid-19 pandemic with the help of the Edmodo and Classdojo platforms. This study aims to determine whether the active learning and learning achievement of students who are subject to learning using Edmodo is better than online learning using Classdojo. The research design used quantitative with quasi-experimental. Collecting data through questionnaires on learning activity and student achievement tests. The results of the multivariate t-test and univariate t-test showed that learning activity using Edmodo was better than student learning activity using Classdojo. The learning achievement of students who use Edmodo in learning mathematics is better than that of students who use Classdojo. Keywords: Learning Edmodo, Learning Classdojo, Online Learning